Vicinal diketones and their precursors in wine alcoholic fermentation: Quantification and dynamics of production. (January 2018) - Ochando, Thomas; Mouret, Jean-Roch; Humbert-Goffard, Anne; Sablayrolles, Jean-Marie; Farines, Vincent
Abstract: Vicinal diketones produced during wine fermentation influence the organoleptic qualities of wine. Diacetyl and 2, 3-pentanedione are well known for their contribution to butter or butterscotch-like flavours. We developed an analysis method to quantify vicinal diketones and their precursors, α-acetolactate and α-acetohydroxybutyrate, under oenological conditions. Five-fold dilution of the sample in a phosphate-citrate buffer (pH 7.0) strongly attenuated matrix effects between the beginning and end of alcoholic fermentation and protected the sample from spontaneous precursor decarboxylation. The use of diacetyl- d 6 as an internal reference improved precision by eliminating differences in the derivatization and extraction yields between the internal standard and the analytes. We obtained unexpected results for alcoholic fermentation by Saccharomyces cerevisiae using this approach. Indeed, the level of diacetyl and 2, 3-pentanedione throughout fermentation were very low. However, we observed a large quantity of both precursors. The production dynamics of α-acetolactate were unconventional and there were two distinct phases of accumulation. The first corresponded to the growth phase, and the second to glucose depletion. There was a rapid decrease of precursor levels at the end of fermentation, but there was still a significant amount of α-acetolactate. The amount of precursor remaining at the end of fermentation constitutes a potential source of diacetyl during wine maturation. α-Acetohydroxybutyrate accumulated during the growth phase followed by a continuous decrease of its concentration during the stationary phase. Residual quantities of α-acetohydroxybutyrate found in wine at the end of fermentation does not constitute a sufficient source of 2, 3-pentanedione to affect the aromatic profile. Graphical abstract: Highlights: Chronology of synthesis of vicinal diketones in wine alcoholic fermentation. Dynamic of production of α-acetohydroxy acids for wine alcoholic fermentation. Adaptation and improvement of GC/MS method to oenological conditions. Residual precursors constitute potential sources of vicinal diketones in wine.